EFFECT OF EXTRUSION ON ESSENTIAL AMINO ACIDS PROFILE AND COLOR OF WHOLE-GRAIN FLOURS OF QUALITY PROTEIN MAIZE (QPM) AND NORMAL MAIZE CULTIVARS - PAES, MARIA CRISTINA DIAS; MAGA, JOSEPH (REVISTA BRASILEIRA DE MILHO E SORGO, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif]–> Whole-grain flours of Quality Protein Maize (QPM) and normal maize were extruded under controlled conditions in order to evaluate the effect of extrusion on the essential amino acids profile and color of the raw material used in the production of maize based extrudates. Flours were conditioned to 150g/kg moisture and processed in a single screw extruder at a screw compression ratio of 3:1, screw speed of 80 rpm, and die head temperature of 1300C, using two different die nozzle diameters (3 and 5 mm). Extrusion caused a diminishment in the contents of the essential amino acids isoleucine, leucine, lysine, threonine and valine when compared to their original flours (P< 0.05). But, the contents of histidine, methionine, phenylalanine and tryptophan were not different for flours and extrudates of the same source (P> 0.05).QPM samples, either raw or extruded, were significantly higher in lysine, methionine and tryptophan compared to samples of normal maize (P< 0.05). Extrudates produced with yellow QPM flours were lighter than their correspondent raw material (P< 0.05) , different from that of yellow normal maize. This trend was also observed for redness (a values) in extrudates. On the other hand, white and yellow extrudates presented higher b values (yellowness) than their correspond raw flour. Despite the adverse effect of extrusion in the amino acid retention, the use of QPM flours in replacement of normal maize flours can provide maize extrudates with superior protein quality.